Marked reduction in haemoglobin levels secondary to ceftizoxime‐induced immune haemolytic anaemia in diabetic patients. (21st April 2020) - Wu, Shengjie; Jing, Li; Feng, Yipeng; Chen, Liping
Abstract: What is known and objective: Drug‐induced immune haemolytic anaemia (DIIHA) is rare and difficult to diagnose. In diabetic patients, the diagnosis of DIIHA is even harder. In the current study, we report on two cases of ceftizoxime‐induced immune haemolytic anaemia in diabetic patients. Case description: Two diabetic patients (suffering from type 1 and type 2 diabetes mellitus, respectively) presented with rapid reduction in haemoglobin levels when exposed to ceftizoxime (2g q12h). They both achieved symptom improvement after switching to another antibiotic. What is new and conclusion: The persistently reduced haemoglobin levels in diabetic patients may contribute to DIIHA. Reviewing patients' medical records might provide some valuable clues as to the causes of DIIHA. Abstract : Drug‐induced immune haemolytic anaemia (DIIHA) is rare and difficult to diagnose, especially in diabetic patients. In the current study we report on two cases of ceftizoxime‐induced immune haemolytic anaemia in diabetic patients. Attention should be paid to the persistently reduced haemoglobin levels, which may contribute to the DIIHA.